Perceptions of libraries and information resources a report to the OCLC membership - De Rosa, Cathy; OCLC. (Dublin, Ohio OCLC Online Computer Library Center, 2005)
This report to the OCLC membership summarizes findings of an international study on information-seeking habits and preferences. It provides the findings and responses from an online survey in an effort to learn more about library use, awareness and use of library electronic resources, the Internet search engine, the library and the librarian, free vs. for-fee information, and the "library" brand.
Introduction -- |g Part 1. |t Libraries and information sources - use, familiarity and favorability -- |t Library use -- |t Familiarity with and usage of multiple information sources -- |t How respondents learn about new information sources -- |t Impressions of information sources -- |g Part 2. |t Using the library - in person and online -- |t Activities at the library -- |t Awareness of library electronic resources -- |t Using library electronic information resources -- |t Seeking assistance in using library resources -- |t Familiarity with the library web site -- |t The internet search engine, the library and the librarian -- |t Keeping up-to-date with library resources -- |g Part 3. |t The library brand -- |t The value of electronic information resources -- |t Judging the trustworthiness of information -- |t Trust in library resources and search engines -- |t Free vs. for-fee information -- |t Validating information -- |t Libraries - positive and negative associations -- |t Lifestyle fit -- |t Books - the library brand -- |t Brand potential - libraries, books and information -- |g Part 4. |t Respondents advice to libraries -- |t The library?s role in the community -- |t Rating library services -- |t Advice to libraries -- |g Part 5. |t Libraries - a universal brand? -- |t Conclusion -- |g Appendix A. |t Supporting data tables -- |g Appendix B. |t Sample verbatim comments -- |t About OCLC.
Keywords: Libraries -- Public opinion; Library users -- Attitudes; Libraries -- User satisfaction -- Statistics; Library use studies; Library surveys